Notes from Self‑Isolation: Imagination in Times of Ruptures - Hawlina, Hana; Zittoun, Tania (Springer Science and Business Media LLC, 2025)
The Covid-19 pandemic brought about an unprecedented global health crisis, which caused a seismic disruption of people’s lives, their habitual practices, systems of meanings, and relationship to the past and the future. This contribution will explore how a group of 17 participants who wrote a collective diary during the first wave of the Covid-19 pandemic in Slovenia (March–May 2020) experienced the crisis as a personal and collective rupture, and what were the functions of the imagination in managing uncertainty, constructing new meanings, and ultimately adapting to the novel situation. Based on the diary data, we find that the global pandemic crisis was experienced as a rupture along four central dimensions: temporality, spatiality, sociality, and embodiment. Drawing on the conceptualisation of the imagination in sociocultural psychology, we have identified the functions of the imagination in different stages of adaptation to the rupture (e.g., experiencing the rupture, meaning-making, distanciation, symbolic mobility, temporal projection), and observed how people use symbolic resources to make sense of the situation, cope with the uncertainty, and construct new imaginings of the future. We thus posit that the imagination plays a central role in repairing ruptures, both in terms of semantic reconfiguration and guiding future-oriented action.
Keywords: COVID 19; Imagination; Diary; Symbolic resource; Longitudinal; Sense-making; Collective diary